Development of service tool failure mode and effect analysis (STFMEA) module for automotive service centers - Syahrial, Erialdi (2011)
Failure Mode and Effect Analysis (FMEA) is one of well-known quality tools, which evolved gradually since its inception in NASA aerospace industry in the year 1963. Then,it has spread to the automotive industry to quantify and prevent possible potential failures at the early stage before reaching the customer. Based on a survey conducted at selected Malaysian automotive service centres, the result shows that the actual service tools utilization by service personnel was only 14.2%. That means the service procedures that performed by service personnel were not followed the service requirements and it could cause to a safety issue to the service personnel, customer and vehicle. Besides that, the service personnel are lack of technical knowledge on FMEA implementation and less awareness on the effect of not using service tools during service or repair. The objective of this study is to establish Service Tool Failure Mode and Effect Analysis (STFMEA) Module for Malaysia automotive industry in order to identify potential failure modes, potential effects, potential causes, service control detection and service control prevention. In this research, a new Occurrence Rating Table and STFMEA Datasheet were developed first in order to support the STFMEA Module development. A car automotive company is known as VATA was selected and four (4) of the VATA service centres were identified as case study companies. The two most available service tool’s brand, known as ‘Service Tool A and ‘Service Tool B’ tools were selected and they became the focus items at each of identified service centres. During the initial study, a FMEA awareness survey was conducted and 98% of users fully understood about the FMEA application and advantages. Another survey was conducted to all users on the new Occurrence Rating Table and as a result, 98% of users answered correctly the questions related to new Occurrence Rating Table application. From the analysis conducted in four (4) VATA service centres, the highest Risk Priority Number (RPN) is 700. Towards ensuring the STFMEA Module is easy to be applied and do not affect the daily servicing tasks, the module was established in Microsoft Excel with some information linked to pdf file format as agreed by all the 23 service personnel during STFMEA Module presentation and actual application. The advantages of the module are the users can directly access all the FMEA datasheets, understand the potential risks and captured service tool technical information immediately. According to the end users feedback during STFMEA Module survey, 100% of the participated service personnel agreed that they could understand all the potential failure modes easily as well as realise with all the potential effect if the service tool is not being used during after sales service. All these feedbacks show that the developed Service Tool Failure Mode and Effect Analysis (STFMEA) Module is a very valuable and user-friendly quality tool for after sales service personnel at VATA service centres.